Redescription of the tadpole of Thoropa taophora (Miranda-Ribeiro) (Anura: Cycloramphidae) - Moura, Pedro Henrique Areco Gomes; Da Rocha Alves, Sérgio Júnior; de Souza E Sousa, Daniela Das Graças; Correa, Claudia Neves; Nunes, Ivan (Zootaxa, 2019)
Thoropa Cope is an anuran genus of the family Cycloramphidae that comprises six species of small rock frogs peculiar for the semiterrestrial habits of their larvae, which develop on wet rock environments distributed throughout eastern and southeastern Brazil (Bokermann 1965; Frost 2019). Current knowledge on their tadpoles relies mostly on their descriptions, namely the works of Bokermann (1965) for T. lutzi Cochran and T. petropolitana (Wandolleck), Caramaschi & Sazima (1984) for T. megatympanum Caramaschi & Sazima, Cocroft & Heyer (1988) for T. saxatilis Cocroft & Heyer, and Barth (1956) and Fatorelli et al. (2018) for T. miliaris (Spix). Thoropa taophora (Miranda-Ribeiro) tadpoles were originally described by Bokermann (1965) as T. miliaris, but several features were overlooked. In addition, T. taophora was recently removed from the synonymy with T. miliaris (Feio et al. 2006). Herein, we present a complete redescription of the tadpoles of T. taophora and provide comparisons with previously published drawings and descriptions of all other species of the genus.